Gestión de recursos humanos y la eficiencia del Programa JUNTOS en la ciudad de Iquitos 2024 - Hidalgo Mozombite, Helen María (2025)
The present research aimed to evaluate the relationship between Human Re sources Management and the efficiency of the JUNTOS Program in the city of Iquitos during the year 2024, the research has a quantitative approach with a non-experimental design and a cross-sectional design, with a correlational study scope; It included 90 workers as a population and sample, including staff from the human resources management office and managers of the JUNTOS Program in the city of Iquitos, the results show that the surveys revealed that the majority of staff consider that expense control policies are correctly applied, and that internal communication is fluid, accessible and efficient, which strengthens coordination and improves response time to beneficiaries' re quests. In addition, the use of technological tools and the clarity of the service channels, both internal and towards the beneficiaries, are positively valued. It was concluded that human resources management significantly influences the efficiency of the JUNTOS Program, highlighting a very strong and positive cor relation between both variables (Spearman's Rho = 0.902). Among the dimen sions evaluated, training (Rho = 0.889), supervision and evaluation (Rho = 0.858), and recruitment and selection of personnel (Rho = 0.803) showed di rect and significant relationships with program efficiency, confirming that hu man capital is a strategic pillar.